"Fraternal" nations and challenges to sovereignty in Ukraine: The politics of linguistic and religious ties. (August 2014) - WANNER, CATHERINE
<x xml:space="preserve">Abstract</x> Vladimir Putin's recent assertions that Russian "compatriots" were suffering in Ukraine contributed to a rapid escalation of instability and violence in this borderland country that defines the margins of Europe and the edge of Eurasia. After 23 years of independence, Ukraine retains significant regional diversity and strong local identities. At the same time, social differences understood in terms of ethnicity, language choice, and religious affiliation have become less defined, as Ukrainians have embraced fluid linguistic and religious practices that defy easy characterization. On the basis of long‐term fieldwork in Ukraine, I argue that "non‐accommodating bilingualism" and "ambient faith" characterize everyday linguistic and religious practices in this postcolonial, post‐Soviet‐socialist space. This flexibility is adaptive domestically. Paradoxically, it contributes to the vulnerability of Ukrainian sovereignty when polarizing, politicized categories based on supposedly identifiable cultural attributes inject a spurious precision into everyday practices with the aim of redefining state sovereignty. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>